PENINGKATAN HASIL BELAJAR IPA SISWA KELAS V SEKOLAH DASAR MELALUI MODEL GENERATIF BERBANTUAN MEDIA ANIMASI - Zahra, Atila; Nurhayati; Dina Dahliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research was conducted to address the low science learning outcomes of fifth-grade elementary school students. The preliminary data showed that the average pre-test score was 50.91, with only 18.18% of students (2 out of 11) achieving the minimum mastery criterion (75), indicating that students’ achievement was still in the low category. This study aimed to improve students’ science learning outcomes through the implementation of the Generative Learning Model assisted by animation media. The research was carried out in two cycles, each consisting of planning, acting, observing, and reflecting stages. The subjects of the study were 11 fifth-grade students of SD Negeri 07 Muaro Kalaban in the 2025/2026 academic year. Data were collected through written tests and observation sheets, then analyzed using descriptive quantitative analysis to determine the mean score and classical learning completeness. The results revealed a significant improvement in students’ learning outcomes. In Cycle I, the mean score increased to 68.18 with classical completeness of 54.55% (6 students achieving mastery). In Cycle II, the mean score further improved to 84.55, and classical completeness reached 90.91% (10 students achieving mastery), exceeding the predetermined success indicator of 75%. Therefore, the implementation of the Generative Learning Model assisted by animation media effectively improved the science learning outcomes of fifth-grade elementary school students.